REKLAMASI SINGAPURA TERHADAP KEDAULATAN WILAYAH REPUBLIK INDONESIA BERDASARKAN HUKUM LAUT INTERNASIONAL - FELLA DEFILLA; Dodi Haryono; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Indonesia is the largest archipelago in Southeast Asia which borderswith Malaysia and Singapore. As a state directly adjacent, not infrequenlyIndonesia seized conflict with the neighboring countries, including borderconflicts. Singapore has conducted reclamation activities sice 1966. The case ofreclamation conducted by Singapore is related to the Law of Sea Convention1982. As the one reference for countries experiencing problem or conflict overmarine areas. Indonesia as one of the countries that have ratified UNCLOS in1982, of course, can make a reference in the 1982 UNCLOS reclamation issue.The purpose of this thesis are; First, to determine the settings reclamation ininternational maritime law; Second, to determine the reclamation by Singaporecould threaten the sovereignty of the Republic Indonesia based on theInternational Law of theSea.Type of research used in this study, using a normative legal research. Atthis research the author concentrated on research that examines the level ofsynchronization law more in the case of sea reclamation in accordance withInternational Law and the connected the bilateral agreements between Indonesiaand Singapore with UNCLOS 1982.The result of the research, conclude two main points, First, in the UnitedNations on the Law of Sea in 1982 there were four of Article related toreclamation activities namely, Article 11, Article 56, pargraph 1, letter b, Article60, and Article 80. Secondly, reclamation conducted by Singapore can notthreaten the sovereignty of the Republic Indonesia unfder Article 11 and 60 poin 8of the United Nations on the Law of the Sea 1982.Keyword: Reclamation, Sovereignty, International Sea or UNCLOS